THE ENHANCEMENT OF COMMUNICATING AND INFERRING SKILLS IN OXIDATION REDUCTION REACTIONS CONCEPT BY PREDICT-OBSERVE-EXPLAIN LEARNING MODEL - putu apriliantika; chansyanah diawati; Ila Rosilawati (Universitas Lampung, 2012)
This research was to describe the effectiveness of the Predict-Observe-Explain (POE) learning model on the oxidation reduction reactions concept to enhance communicating and inferring skills. The effectiveness of the POE learning model in this research indicated with the significant difference between the experimental class with the control class. The population in this research are all students of the class X Senior High School Paramarta 1 in Seputih Banyak academic year 2011-2012, totall of all students are 150 and to spread into three classes they are X1, X2, and X3. The sample in this research are X1 and X2 class. This research used method the quasi-experimental and non equivalent control group design. analysis data in this research of the hypothesis testing by using two different average test. The results of the hypothesis testing that the average value of n-gain communicating and inferring skills on the oxidation-reduction reactions concept of students applied learning POE higher than students who applied to conventional learning. Thus, it can be concluded that the POE model learning on the oxidation-reduction reactions concept effective in increasing communicating skills and inferring skills in the Senior High School Paramarta1 2011/2012.Keywords: Predict-Observe-Explain (POE),communicating skill and inferring skill